Catholic and Tamil Divine Mothers: Mary and the Village Goddess - Granziera, Patrizia (International journal of Asian christianity, 2023)
The cult of the Virgin Mary in southern India and especially in Tamil Nadu is very popular, and she certainly incarnates the emblematic figure of contemporary Indian Catholicism. After the arrival of the Portuguese in India, the task of evangelization was in the hands of the missionary orders who worked under Portuguese rule. In the seventeenth century, the centre of interest in Christian missions in India moved southwards to the Tamil country. It was the Jesuits who ruled and administered over the area for the next century or so. They contributed to the assimilation of the Virgin Mary into the Tamil villagers’ pantheon, trying to translate the Catholic conception of the divine into Tamil and locating the Catholic faith at “home” in the Tamil world. This study will try to explain how missionaries succeeded in spreading the cult of a new Catholic female deity among devotees of the grama-devatas.